Tablet computer-based cognitive training for visuomotor integration in children with developmental delay: a pilot study - Jee Hyun Suh; Soo Jeong Han; Sun Ah Choi; Hyesung Yang; Sihyun Park (BMC, 2024)
Abstract Background Impaired visuomotor integration (VMI) is commonly observed in children with developmental delay (DD). This pilot study aimed to evaluate the effects of tablet computer-based cognitive training on the VMI in children with DD. Methods This study included children aged 4 to under 18 years diagnosed with DD. The children participated in a 12-week tablet computer-based visual-spatial and visuomotor training program. They were administered the Mind Rx Kids Program (Brain Academy, Seoul, South Korea). The participants underwent daily 30-min tablet computer-based training for 12 weeks. The primary visuomotor function was measured using the Beery-Buktenica Developmental Test of Visual-Motor Integration, 6th Edition (VMI-6). For secondary outcomes, measurements were taken before and after 12-week treatment using the Quality of Upper Extremity Skills Test (QUEST), Functional Independence Measure for Children (WeeFIM), Childhood Autism Rating Scale (CARS), Attention deficit hyperactivity disorder Rating Scale (ARS), and Child Smartphone Addiction Observer Scale. The Wilcoxon signed-rank test was used to compare the pre- and post-treatment outcomes. Results Ten children with DD participated in this study. The results of the 12-week tablet computer-based cognitive training showed significant improvements in the raw score, standard score, percentile score, and equivalent age of the Beery VMI-6. Additionally, there were significant improvements in QUEST and WeeFIM scores. Although there were improvements in the CARS, ARS, and smartphone addiction observer scale, these were not statistically significant. Conclusion This pilot study confirmed that applying tablet computer-based cognitive training to children with DD not only improves VMI, but also enhances fine motor skills and activities of daily living. Furthermore, the results of this study indicate that tablet computer-based cognitive training does not increase digital media addiction. Therefore, children with DD can engage in tablet computer-based cognitive training at home without concerns about digital media addiction.